Digital economy’s role in shaping China’s outward investment in Belt and Road countries - Tang, Wan; Lan, Qingxin; Yang, Yalin (Technological and Economic Development of Economy, 2025)
Previous international investment-related literature is less likely to include host country digital economy as an influential factor in the analysis framework. Meanwhile digital economy-related literature mainly focuses on the concept and characteristics of digital economy, and few scholars explore the impact and mechanism of China’s OFDI in the context of digital economy. Based on the theory and mechanism analysis, this article first constructs a comprehensive digital economy indicator system using data from 46 B&R countries from 2004 to 2020 and then constructs extended investment gravity model, technological innovation intermediary impact and trade cost moderating effect to thoroughly investigate the effect and fundamental mechanism of digital economy on China’s OFDI. The conclusions are as follows: First, digital economy indicators’ computation reveals significant disparities among B&R countries. Second, baseline regression finds that B&R countries’ digital economy considerably boosts China’s OFDI. Third, regional heterogeneity reveals that digital economy in ASEAN countries plays a more visible role in boosting China’s OFDI. Fourth, mechanism analysis reveals that B&R countries’ digital economy can encourage China’s OFDI by improving technological innovation and reducing trade costs. First published online 6 December 2024